Deciphering age and origin of gullied-shaped landscapes in Sierra de las Nieves National Park (South of Spain) - Martínez-Murillo, Juan Francisco; Carruana-Herrera, David (My University, 2022)
This study aims to shed light on the age and origin of these gullied and badland morphologies located in the upper area from the Sierra de las Nieves National Park. Origin of gullies and badlands usually is related to either climate or human activity shifts, more common in cold regions the former whilst in semiarid regions the latter. In this case, Sierra de las Nieves, mainly of built on calcareous rocks, is characterised by Mediterranean mountain climate and a long tradition of human activity in previous centuries. The experimental area is located in its upper part forming plateu-like relief where calcareous hills are separated by valleys of lower slopes filled with marls and quaternary sediments. Gullies and badlands are located in these materials. Vegetation corresponds to an opened-mixed vegetal formation of Quercus Faginea and Abies pinsapo Boiss. with typical high mountain shrubs and meadows. To carry out the study, one transect was defined in one selected gullied-area including 15-sampling points and ecogeomorphology described: vegetation, soil surface conditions, and geomorphic processes. In addition, soils were also sampled in depth at the same points and some properties analysed in laboratory. The transect run along the maximum slope line from one hill to the valley bottom and continue towards the top of the opposite hill. In the valley bottom, there was a fluvial Quaternary deposit covering and fossilising the marls formation. When outcropped, these marls were affected by concentrate water erosion forming gullies. Also, its surface developed typical morphologies of Badlands: cracks and crusts in dry conditions, short and shallow mudflows in wet conditions, and popcorn in winter. In that deposit, samples were taking in depth until the marls was reached and dated by means C14 technique. Ecogeomorphology inventory, soil properties, and datations have been used to shed light on the age and origin of the formation of gullies and badlands.
Keywords: Geomorfología; Suelos; Sierra de las Nieves; Cárcavas; Datación